Predictors of Pulmonary Oxygenizing Function during Uncomplicated Operations under Extracorporeal Circulation - A. A. Romanov (Общая реаниматология, 2007)
Objective: to reveal the statistically significant predictors affecting the oxygenation index (PaO2/FiO2) in the post-perfusion period during uncomplicated operations under extracorporeal circulation (EC).Subjects and methods. Seventy-eight patients aged 37 to 73 years in whom myocardial revascularization was made during uncomplicated operations under EC were examined. The parameters of artificial ventilation (AV) and lung biomechanics were recorded in real time on a KION 6.h. or a Servo-i monitoring system. Demographic and clinical indices, such as age, body mass index (BMI), baseline PaO2/FiO2, and statistical thoracopulmonary compliance (Cst), a history of chronic obstructive pulmonary diseases, smoking, operation duration, EC, myocardial ischemia, mammary coronary anastomosis (MCA), and blood hydrobalance at the end of an operation, were assessed for impact on PaO2/FiO2. Univariate regression analysis calculating the pair linear correlation coefficient (r) and multiple linear regression were made to comparatively assess the predictive values of different indices in decreasing PaO2/FiO2.Results. Univariate regression analysis indicated that the significant predictors of uncomplicated pulmonary oxygenizing function were BMI (p=0.008), PaO2/FiO2 (p<0.001), and Cst (p<0.001) after tracheal intubation. Multiple linear regression evaluating the influence of pre- and intraoperative factors on PaO2/FiO2 showed that the significant predictors were BMI (p=0.012), MCA (p=0.006), and EC duration (p=0.044). A significant correlation was found between the duration of EC and the level of PaO2/FiO2 (r=-0.87; p=0.00045) under more than 130-min EC.Conclusion. During uncomplicated operations under EC for coronary heart disease, the statistically significant predictors of postperfusion PaO2/FiO2 are mainly the state of the respiratory system (the values of PaO2/FiO2 and Cst just after tracheal intubation), BMI, more than 130-min EC, and MCA.